Physicochemical Changes and Role of Analytical Chemistry in Black Garlic (Allium sativum L.) Processing - Wonorahardjo, Surjani; Sari, Dian Puspita; Salsabila, Arini; Estiyawati, Estiyawati; Yuliani, Dewi; Wijaya, Anugrah Ricky; Suharti, Suharti; Kusumaningrum, Irma Kartika; Maharani, Chariztya Anggita; Noviyanti, Thjiong Angelina (UI Scholars Hub, 2023)
Black garlic is a traditional spice having potential of herbal medicine; however, continuous heating darkens its color and changes its taste due to chemical processes and new equilibrium in the system. In this study, fresh garlic was processed into black garlic at 60 °C for 24 days. Changes in physical and chemical parameters, such as browning and protein content, reducing sugar content, and antioxidative components were recorded. Protein content was measured by Kjeldahl method, brown color development was analyzed using a color reader, reducing sugar was examined using a dinitro salicylic DNS reagent, and antioxidative activities were studied with a diphenyl picrylhydrazyl DPPH reagent in terms of their percent inhibition. Gas chromatography – mass sepctrometry (GC–MS) and Liquid Chromatography-High Relosultion Mass Spectrometry (LC–HRMS) were performed to determine the chemical profiles. Results showed a number of interesting features. The protein and sugar contents increased up to 3 and 4 times that of the initial values, respectively during processing. The antioxidative properties improved in the later stages. The chemical profiles of volatile and nonvolatile components were altered in their final stage. Sulfur and nitrogen-containing nonvolatile components were relatively stable during heating, but their compositions changed. The natural chemical changes reflect the biological potential dynamics in biological processes as herbal supplements. The reflection of the processes might go further into food chemistry and the food industry. This needs an interdisciplinary approach, expanded to biological concepts and safe, ethical industrial processes.